Umkm Survival Strategy During The Covid-19 Pandemic (Case Study Of Kober Mie Setan Jember Branch) - Afnas Fahrurrasi (Department of Islamic Economics, Postgraduate Program, UIN Kiai Haji Achmad Siddiq, Indonesia, 2024)
The condition of UMKMs is currently starting to improve compared to 2019. In 2020, some have started to move towards recovery, but some other UMKMs are still in decline. The impact of the Covid-19 pandemic is not only on the manufacturing sector, but also on the UMKM sector since April 2020. One of the national economic recovery efforts carried out by the government during the Covid-19 pandemic is to encourage the UMKM sector. The focus of this study is 1) How is the survival strategy at Kober Mie Setan Jember branch, 2) How is the SWOT Analysis of Kober Mie Setan Jember branch), The purpose of this study refers to the results of a field review at the UMKM Campus Environment in Jember Regency which includes: 1) To analyze the survival strategy at Kober Mie Setan Jember branch. 2) To analyze the SWOT of Kober Mie Setan Jember branch. This study uses a qualitative approach method with a type of field research (case study). In the implementation of data collection with several stages such as interviews, observations and documentation. The analysis of research data used is descriptive qualitative research. This qualitative research is based on fieldwork, supported by theory and bibliography. The analysis was conducted through condensation, data presentation, data verification, and triangulation to validate the data. The results of this study indicate that: 1) Kober Mie Setan Jember's survival strategy for maintaining its business during the COVID-19 pandemic includes product, location, pricing, and promotional strategies. 2) The SWOT analysis of Kober Mie Setan indicates that it is highly feasible to operate its business.